Interaction of ubiquitin ligase CBL with LMP2A protein of Epstein-Barr virus occurs via PTB domain of CBL and does not depend on adaptor ITSN1 - Dergai, O.V.; Dergai, M.V.; Gudkova, D.O.; Tsyba, L.O.; Skrypkina, I.Ya.; Rynditch, A.V. (Вiopolymers and Cell, 2013)
Aim. Previously Latent membrane protein 2A (LMP2A) of Epstein-Barr virus was found to be ubiquitylated by CBL ubiquitin ligase but no direct interaction of LMP2A with CBL was reported. We aimed to explore this interaction and study a possibility of adaptor protein involvement. Taking into consideration that both LMP2A and CBL were shown to interact with endocytic adaptor protein intersectin 1 (ITSN1), we assumed that the latter could serve as a scaffold for LMP2A/CBL complex. Methods. We used an immunofluorescence and coimmuno- precipitation approaches to test a mutual complex formation of ITSN1, CBL and LMP2A proteins. Results. LMP2A coimmunoprecipitated with CBL while LMP2A did not interact with CBL G306E mutant harboring inactive phosphotyrosine-binding domain. We observed a triple colocalization of ITSN1, CBL and LMP2A signals in MCF-7 cells as well as coprecipitation of all mentioned proteins. Overexpression of ITSN1 did not affect the efficiency of complex formation of LMP2A with CBL. Moreover, LMP2A mutant unable to interact with ITSN1 was readily precipitated with CBL. Conclusions. LMP2A can be engaged in the complex together with endocytic adaptor ITSN1 and ubiquitin ligase CBL. We show that PTB domain of CBL is responsible for interaction with LMP2A. ITSN1 is not required for LMP2A recruiting to CBL. Відомо, що мембранний білок латентної фази 2А вірусу Епштейна-Барр убіквітинілюється убіквітин-лігазою CBL, хоча прямої взаємодії цих двох білків не виявлено. Наша мета полягала у дослідженні взаємодії LMP2A і CBL та вивченні можливості участі в цьому комплексі білкового адаптера. Беручи до уваги, що обидва зазначених білки взаємодіють з ендоцитозним адаптерним білком ITSN1, ми припустили, що останній може слугувати платформою для утворення комплексу LMP2A/CBL. Методи. Імунофлуоресцентний аналіз та коімунопреципітацію застосовано для дослідження можливості формування комплексу між ITSN1, CBL і LMP2A. Результати. Коімунопреципітація LMP2A і CBL свідчить про утворення комплексу цими білками, причому мутантна форма CBL, яка не здатна зв’язувати фосфотирозинові залишки, не взаємодіє з LMP2A. Ми спостерігали потрійну колокалізацію ITSN1, CBL і LMP2A у клітинах лінії MCF-7, а також коімунопреципітацію всіх зазначених білків. Надекспресія ITSN1 не впливає на ефективність коімунопреципітації LMP2A з CBL. Більш того, мутантний варіант LMP2A, не здатний зв’язуватися із ITSN1, ефективно взаємодіє з CBL. Висновки. LMP2A може входити до комплексу ендоцитозного адаптерного білка ITSN1 та убіквітин-лігази CBL. Участь ITSN1 не є необхідною для формування комплексу між LMP2A і CBL. Показано, що РТВ-домен убіквітин-лігази CBL відповідає за зв’язування з LMP2A. Известно, что мембранный белок латентной фазы 2А вируса Эпштейна-Барр убиквитинилируется убиквитин-лигазой CBL, однако прямого взаимодействия этих белков ранее обнаружено не было. Наша цель состояла в исследовании взаимодействия CBL и LMP2A, а также в изучении возможности участия в этом комплексе белкового адаптера. Принимая во внимание, что оба упомянутых белка взаимодействуют с эндоцитозным адаптерным белком ITSN1, мы предположили, что последний может служить платформой для образования комплекса LMP2A/CBL. Методы. Иммунофлуоресцентный анализ и коиммунопреципитацию использовали для изучения возможности образования комплекса с участием ITSN1, CBL и LMP2A. Результаты. Коиммунопреципитация CBL и LMP2A свидетельствует об образовании комплекса этими белками, причем мутантная форма CBL, лишенная способности связывать фосфотирозиновые остатки, не взаимодействует с LMP2A. Мы детектировали тройную колокализацию ITSN1, CBL и LMP2A в клетках линии MCF-7, а также ко-иммунопреципитацию вышеупомянутых белков. Суперэкспрессия ITSN1 не влияет на эффективность копреципитации CBL и LMP2A. Более того, мутантный вариант LMP2A, дефектный по связыванию с ITSN1, эффективно взаимодействовал с CBL. Выводы. LMP2A может включаться в комплекс эндоцитозного адаптера ITSN1 и убиквитин-лигазы CBL. Участие ITSN1 не является обязательным для образования комплекса LMP2A/CBL. Показано, что РТВ-домен убиквитин-лигазы CBL отвечает за связывание с LMP2A.